Penerapan Teknologi Instalasi Pengolahan Air Payau dengan Filtrasi Serbuk Kerang Darah (Anadara granosa) di Kampung Dangas, Tanjung Pinggir Batam - Rahmiati, Sari; Sunarsono, Hery; Rahman, Taufiq; Oktafebrian, Febby; Hutagalung, Nicholas Bramuly (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2025)
Background: Brackish water is a unique ecosystem formed from the mixing of seawater and freshwater, commonly found in coastal areas and swamps. However, its existence is now threatened by heavy metal pollution from industrial activities. Unprocessed heavy metals are discharged into brackish water, contaminating the ecosystem and endangering human health, especially coastal communities that rely heavily on this water resource. Methods: To address this problem, the Community Service Program (PkM) proposes the application of a water treatment installation technology based on blood cockle shell powder filtration in the area of the Indonesian Traditional Fishermen’s Union (KNTI), specifically in Dangas Village, Batam. Blood cockle shells (Anadara granosa) were chosen because of their high calcium carbonate (CaCO₃) content and their effectiveness in absorbing heavy metals. Results: Based on p-value analysis, there was a significant difference in partner satisfaction before and after the PkM activity. Conclusion: This approach is expected to provide an environmentally friendly and sustainable solution to combat brackish water pollution, improve the quality of life of coastal communities, and prevent long-term health impacts caused by heavy metal exposure.